Elements of religious belief and social values among the laity of the church in Wales - Richard Startup (Journal of Contemporary Religion, 1997)
This paper explores the relationship between religious beliefs and secular attitudes of lay people within a single church, the Anglican Province of Wales (UK). The origins of the data are described and findings as to the distinctive social characteristics of the laity reported. Results of the analysis of the interrelationship between different dimensions of religious belief are reported and discussed. The secular attitudes of the laity are compared with those of the British population, and found to be on the whole more ‘liberal’. While some differences between the secular attitudes of the laity and the general population are clearly related to the distinctive social position of the former, social location is unable to explain all of these differences. A number of relationships between belief and secular attitudes are described. Anglicans with more ‘catholic’ beliefs seem more concerned in their secular attitudes with issues which they perceive as involving rule breaking or attitudes to authority, while ‘evangelicals’ react more strongly to what can be interpreted as unconscionable behaviour.